Gluteus maximus tendon transfer for chronic abductor insufficiency: the Geneva technique. Issue 6 (November 2021) - Christofilopoulos, Panayiotis; Kenanidis, Eustathios; Bartolone, Placido; Poultsides, Lazaros; Tsiridis, Eleftherios; Kyriakopoulos, George
Introduction: The treatment options of chronic abductor insufficiency in the setting of muscle degeneration, are limited and technically demanding. We present the outcomes of a salvage technique for unreconstructable, chronic abductor tears performed by a single surgeon. Methods: We retrospectively evaluated 38 patients who were surgically managed for chronic abductor insufficiency. Patients without hip implants and patients following primary or revision total hip arthroplasty (THA) were involved. All patients had a Trendelenburg gait, impaired muscle strength of abduction (⩽M4) and fatty degeneration of muscles (Goutallier ⩾3). They underwent transfer of a flap of the anterior third of gluteus maximus to the greater trochanter that was sutured under the slightly mobilised vastus lateralis. The level of pain, functional scores, muscle strength and Trendelenburg gait were re-evaluated at 12 postoperative months. Results: The mean age of patients was 70.2 years. 10 patients received the tendon transfer on a native hip, 6 following primary THA and 22 after revision THA. The mean pain level (3.2 vs. 7, p < 0.001) and Harris Hip Score (80.2 vs. 41.6, p < 0.001) and the median abductor strength (4 vs. 3, p < 0.001) was significantly improved compared to the preoperative scores. 26 patients demonstrated negative and 12 positive Trendelenburg sign at 12 postoperative months. No serious complications were reported. Conclusions: This salvage technique improved the strength of abduction and functional results and reduced the level of pain in 80% of patients with chronic abductor tears. The short-term outcomes of the procedure were favourable; however, further evaluation is needed.